Natchiq grows up: the story of a ringed seal pup and her changing home - Hauser, Donna D. W., author; Frost, Kathryn J., author; Whiting, Alex, V., author; Goodwin, John, contributor; Harris, Cyrus, contributor; Goodwin, Pearl, contributor; McFarland, Heather, illustrator; University of Alaska Press, publisher (Colorado State University. Libraries, 2023)
Accessible description of the early life and lair of Natchiq, a ringed seal pup near Kotzebue, in northern coastal Alaska. Includes photos and diagrams from seal researchers and science communicators, as well as sidebars focused on Indigenous and Traditional Ecological Knowledge.--Provided by publisher.
Keywords: Ringed seal -- Alaska -- Kotzebue Sound -- Juvenile literature; Ringed seal -- Life cycles -- Alaska -- Kotzebue Sound -- Juvenile literature; Ringed seal -- Infancy -- Alaska -- Kotzebue Sound -- Juvenile literature; Ringed seal -- Habitations -- Alaska -- Kotzebue Sound -- Juvenile literature; Ringed seal -- Habitat -- Alaska -- Kotzebue Sound -- Juvenile literature